2018
DOI: 10.3847/1538-4357/aabe8c
|View full text |Cite
|
Sign up to set email alerts
|

The Dust and [C ii] Morphologies of Redshift ∼4.5 Sub-millimeter Galaxies at ∼200 pc Resolution: The Absence of Large Clumps in the Interstellar Medium at High-redshift

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 88 publications
(232 reference statements)
13
75
0
1
Order By: Relevance
“…11), as well as the Herschel observations of ULIRGs from the GOALS sample (Díaz-Santos et al 2017). However, as the [C ii] emission is significantly more extended than the FIR continuum (in line with Gullberg et al 2018;Rybak et al 2019), the source-averaged [C ii/FIR measurement provides only an upper limit on the [C ii]/FIR ratio in the central, FIR-bright region. The large extent of the [C ii] emission compared to the FIR continuum implies that the spatiallyaveraged [C ii]/FIR measurements in high-redshift sourcesas inferred from unresolved observations -mask the potentially very strong [C ii]/FIR deficit in the actual star-forming regions.…”
Section: [Cii]/fir Ratio and Deficitmentioning
confidence: 93%
“…11), as well as the Herschel observations of ULIRGs from the GOALS sample (Díaz-Santos et al 2017). However, as the [C ii] emission is significantly more extended than the FIR continuum (in line with Gullberg et al 2018;Rybak et al 2019), the source-averaged [C ii/FIR measurement provides only an upper limit on the [C ii]/FIR ratio in the central, FIR-bright region. The large extent of the [C ii] emission compared to the FIR continuum implies that the spatiallyaveraged [C ii]/FIR measurements in high-redshift sourcesas inferred from unresolved observations -mask the potentially very strong [C ii]/FIR deficit in the actual star-forming regions.…”
Section: [Cii]/fir Ratio and Deficitmentioning
confidence: 93%
“…The kinematic parameters agree well with those derived from the previous fitting of a 0.3 ′′resolution [C ii] cube with a channel width of 50 km s −1 (Tadaki et al 2019), implying that measurements of maximum rotation velocity and local velocity dispersion do not require very high-resolution observations even in compact SMGs. This is thanks to the fact that the [C ii] emission is relatively extended compared to the dust continuum and CO line emission (Gullberg et al 2018;Tadaki et al 2019). Given that [C ii] emission is completely resolved out in 0.…”
Section: Residual Components In [C Ii] Line Emissionmentioning
confidence: 99%
“…As multiple studies have found the [CII] deficit to be a local effect (Smith et al 2017;Gullberg et al 2018), we use the extended SPIRE coverage to determine if there are significant differences between the behavior of the phase-separated [CII] deficit in the inner nuclear regions of these galaxies and the more extended disks. In order to test these differences, we divide the BtP regions into 'Inner' and 'Outer' regions, with Inner regions centered within 0.25R 25 and Outer regions as any falling outside of this limit.…”
Section: Inner and Outer Btp Measurementsmentioning
confidence: 99%
“…An intriguing application of an improved [CII]-based SFR indicator lies in the realm of high redshift galaxies. There have been many detections of the [CII] 158 µm line in galaxies from z ∼ 1 to z ∼ 7 Ivison et al 2010;Stacey et al 2010;Graciá-Carpio et al 2011;Valtchanov et al 2011;Gullberg et al 2015;Malhotra et al 2017;Barisic et al 2017;Gullberg et al 2018;Rybak et al 2019). The brightness of the [CII] line enables detections across a wide range of distances, making it a popular tool for probing the PDR properties and kinematics of galaxies in the high-redshift Universe.…”
Section: Introductionmentioning
confidence: 99%